6+2x=6(18+6x)

Simple and best practice solution for 6+2x=6(18+6x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6+2x=6(18+6x) equation:


6+2x=6(18+6x)

We simplify the equation to the form, which is simple to understand
6+2x=6(18+6x)

Reorder the terms in parentheses
6+2x=+(+108+36x)

Remove unnecessary parentheses
+6+2x=+108+36x

We move all terms containing x to the left and all other terms to the right.
+2x-36x=+108-6

We simplify left and right side of the equation.
-34x=+102

We divide both sides of the equation by -34 to get x.
x=-3

See similar equations:

| 12x+5x^2-9x^3=0 | | x^3-36x^2+72x-168=0 | | .25+14=38 | | (3x^4+3x^3-8)-(2x^2-9x+7)= | | -8k-5=2k+15 | | 19x^2+5x+0=0 | | 6w+8=4w+18 | | 14-c=5 | | (2x+y)-(x-4y)= | | x+2=7 | | (9z^3+6z)-(-2z^3-4z+8)= | | x^5+3x^4+2x^3+2x^2+6x+4=0 | | 6(2a^2+3a)=6(3-2a) | | x^5+3x^4c+2x^3+2x^2+6x+4=0 | | -17=3-4n | | 2(-5-3a)=7a+3 | | x^3+8x^2-8x-64= | | ln(x+3)-ln(x-4)=ln(x) | | -32x^2-80x-32=0 | | 3(r+4)+2(r+5)=32 | | 3x-5y=22 | | 15n^2+16n-7=0 | | (9x-2)(9x+2)= | | 27x^3+1000=0 | | -9=2-(5-z) | | 7x^2+-14x-7=0 | | 4+30(12+36+60)=x | | -4(6-w)=-2w-12+4w | | 0.8b=10.4 | | 1+3(16-2x)=0 | | 1+3(16-2x)= | | x+15=-5 |

Equations solver categories